2020
DOI: 10.3390/md18080390
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Study of Marine Products with Lipid-Lowering Properties

Abstract: With twice the number of cancer’s deaths, cardiovascular diseases have become the leading cause of death worldwide. Atherosclerosis, in particular, is a progressive, chronic inflammatory cardiovascular disease caused by persistent damage to blood vessels due to elevated cholesterol levels and hyperlipidemia. This condition is characterized by an increase in serum cholesterol, triglycerides, and low-density lipoprotein, and a decrease in high-density lipoprotein. Although existing therapies with hypolipidemic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 114 publications
0
8
0
Order By: Relevance
“…Fucoxanthin is an oxygen-containing carotenoid compound isolated from brown algae. This compound has been studied as a treatment to prevent the over-oxidation of lipids and restrain their accumulation [ 60 ]. Fucoxanthin also downregulates transcription factors such as peroxisome proliferator activated receptor (PPAR) and sterol regulatory element-binding protein 1c, which are play a role in adipogenesis.…”
Section: Marine Natural Products and Cardiovascular Diseasesmentioning
confidence: 99%
“…Fucoxanthin is an oxygen-containing carotenoid compound isolated from brown algae. This compound has been studied as a treatment to prevent the over-oxidation of lipids and restrain their accumulation [ 60 ]. Fucoxanthin also downregulates transcription factors such as peroxisome proliferator activated receptor (PPAR) and sterol regulatory element-binding protein 1c, which are play a role in adipogenesis.…”
Section: Marine Natural Products and Cardiovascular Diseasesmentioning
confidence: 99%
“…Fucoxanthin is a carotenoid containing oxygen that is extracted from brown algae ( 6 ). Recent studies have suggested that fucoxanthin prevented lipids from overoxidation and restrained the accumulation of lipids.…”
Section: Organic Small Moleculesmentioning
confidence: 99%
“…DSW also restrained adipocyte differentiation, lipogenesis, and adipocytokine gene levels as well as elevated lipolysis and fatty acid oxidation gene levels ( 29 ). Additionally, DSW was reported to decrease serum lipids by inhibiting the levels of TG and TC in serum and suppressing AMPK, PPARα, CPT-1, and ACO expression ( 6 ). Another investigation also indicated that DSW inhibited HMGCR and PCSK9 expression, promoted the phosphorylation of AMPK, and elevated LDLR, SREBP-1α, and SREBP-2 expression ( 6 ).…”
Section: Organic Small Moleculesmentioning
confidence: 99%
“…1,2 Due to the side effects of lipid-lowering drugs (such as statins), the natural products and medicines and edible foods with a strong lipid-lowering ability and low toxicity have attracted more and more attention worldwide. 3,4 Medium-chain triglycerides (MCTs) are generally recognized as safe (GRAS) foods by the US Food and Drug Administration (FDA) and considered as common foods by the National Health Commission of the People's Republic of China and State Administration for market regulation. 5,6 As far as we know, the MCTs have many health benefits because they have unique metabolic pathways, which is different from longchain triglycerides (LCTs) in the body.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In recent years, the accelerated pace of life and excessive calorie intake often lead to metabolic disorders in the body, thereby increasing the risk of metabolic diseases, such as obesity, type 2 diabetes, and cardiovascular diseases (CVDs). CVDs are usually considered as a major cause of mortality at home and abroad. , Due to the side effects of lipid-lowering drugs (such as statins), the natural products and medicines and edible foods with a strong lipid-lowering ability and low toxicity have attracted more and more attention worldwide. , …”
Section: Introductionmentioning
confidence: 99%